Analisis Penyebab Berkurangnya Penggunaan Bahasa Jawa di Kalangan Generasi Muda di Sumatera Utara - Siregar, Dean; Sukma, Ayman Human; Pertiwi, Ayu Amelia; Syaifullah NST, Sarah Putri; Chairunisa, Hera (Universitas Galuh, 2025)
This study analyzes the causes of the declining use of the Javanese language among young generations in North Sumatra. This language shift is influenced by various factors, such as social environment, education, and technology. The study employs a literature review method by examining various relevant sources. The findings indicate that the lack of language transmission from the older to the younger generation is the primary factor contributing to this language shift. A social environment that prioritizes the Indonesian language, along with the lack of educational policies supporting regional languages, further accelerates this process. Additionally, the dominance of social media and technology, which primarily use Indonesian and English, reduces young people's exposure to the Javanese language. The preservation of the Javanese language can be achieved through its integration into formal education, the utilization of technology as a learning tool, and the strengthening of cultural communities. With the synergy of these three aspects, the Javanese language in North Sumatra can still be maintained.